Mapping of the distribution of Mycobacterium bovis strains involved in bovine tuberculosis in Mozambique - Machado, Adelina da Conceicao (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.